2016
DOI: 10.1002/adma.201602479
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte‐Gated Organic Field‐Effect Transistor Based on a Solution Sheared Organic Semiconductor Blend

Abstract: This communication presents a novel electrolyte gated field-effect transistor based on a blend of dibenzo-tetrathiafulvalene and polystyrene deposited through bar-assisted meniscus shearing. This technique allows the fabrication of high performing electronic devices suitable for (bio)sensing applications and might capture industrial interest due to its scalability. The reported devices can operate in aqueous solution with comparable complexity to real samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 32 publications
1
50
1
Order By: Relevance
“…Films with a ratio of DB‐TTF/PS 4:1 and with only DB‐TTF were not considered to work as transistors because the on/off ratio was only about 10 (Figure S12, Supporting Information). This enhanced doping could possibly be caused by the lower amount of PS that prevents an efficient encapsulation of the OSC . Importantly, to our knowledge this is the first time that it has been demonstrated that the ratio OSC: binder polymer has not only an influence on the thin films morphology and crystal size domains, but it can also determine the OSC polymorph or the polymorphism purity.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Films with a ratio of DB‐TTF/PS 4:1 and with only DB‐TTF were not considered to work as transistors because the on/off ratio was only about 10 (Figure S12, Supporting Information). This enhanced doping could possibly be caused by the lower amount of PS that prevents an efficient encapsulation of the OSC . Importantly, to our knowledge this is the first time that it has been demonstrated that the ratio OSC: binder polymer has not only an influence on the thin films morphology and crystal size domains, but it can also determine the OSC polymorph or the polymorphism purity.…”
Section: Resultsmentioning
confidence: 82%
“…It should be also highlighted that typically DB‐TTF thin film OFETs exhibit large threshold voltages ( V TH ), often higher than 20 V, and are very unstable in environmental conditions. However, blending the material with an inert polymer has been shown to be an ideal strategy to fabricate stable DB‐TTF‐based devices …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments were performed in the absence of electron acceptor molecules to investigate the possible effect of the short electrically inactive chain of P4VP and whether the particular NPs preparation conditions using a nonsolvent affect the electrical properties of the conjugated polymer. [44] The hole mobility of BCP5-only NP films was measured in untreated samples and after thermal treatment for 20 min at 90 and 120 °C, respectively.…”
Section: Morphological and Electrical Characterizationmentioning
confidence: 99%
“…In this paper, we report a mercury‐mediated surface doping of a thin film of a p‐type OSC blended with polystyrene (PS) induced by a redox reaction between an aqueous mercury solution (HgCl 2 ) and the OSC. It has been previously shown that the films prepared by these OSC/PS blends are self‐encapsulated by the polymer and, hence, a poor permeation of the ions into the OSC is expected . In order to monitor the doping level, we have exploited the WGOFET layout as electronic transducer.…”
Section: Introductionmentioning
confidence: 99%